“I’m a Mother Who Always Tries to Give My Children Hope”—Refugee Women’s Experiences of Their Children’s Mental Health - Pérez-Aronsson, Anna; Warner, Georgina; Sarkadi, Anna; Osman, Fatumo (Frontiers in Psychiatry, 2019)
Background: The prevalence of mental health problems are high amongst refugee children. Childhood mental health problems have long term negative consequences and costs both for the individual child and society. The present study aimed to explore refugee parents’ experiences of their children’s mental health. Methodology: A qualitative explorative study was conducted. Data were collected through semi-structured interviews with nine refugee mothers who have been in Sweden less than five years and with at least one child in the ages 8-14 years. Data were analysed inductively using thematic network analysis. Results: The global theme that emerged from the analysis was Navigating the moving landscape of forced migration, which described the refugee mothers’ experiences of the previous adversity the family went through, the ongoing transition in the new context and lastly the pathways to promote their children’s mental health. Two organizing themes described mothers’ and children’s navigation of the forced migration: Previous adverse events and new suffering and Promoting children’s well-being. Mothers described aggression and frequent conflicts, or refusal to play or eat, in their children related to living conditions at refugee camps and social isolation. This improved when children started school and possibilities of social relations increased. Mothers’ own mental health and lack of language skills could also have a negative impact on the children. To focus on the present and have hope of the future was helpful to the children. Encouragement and social support from parents, teachers and friends promoted children’s well-being. Conclusion: The role of the host country in the promotion of the mental health of refugee children is emphasized. Interventions aimed to improve peer relations and reduce discrimination are needed, and points to the school as a potential arena for positive change. Parental support groups were also mentioned as helpful in understanding the children’s need for support.